Sangga Buwana as Food Acculturation: Yogyakarta Royal Traditional Food - Marcellus Arnold; Yolanda Victoria Rajagukguk (Universitas Andalas, 2021)
Indonesia has various traditional foods, some of which are the result of acculturation with other countries’ foods. Sangga buwana is the Javanese-Dutch influenced cuisine, which became one of the favorite dishes of the sultans of Yogyakarta. Till date, the publication about sangga buwana is still limited. This paper aimed to introduce and spread the knowledge about sangga buwana as the result of food acculturation, focusing on its history, philosophy, how it is prepared, and its nutritional value. The study was carried out through interviews with the experts and literature review. Sangga buwana consists of several components, including choux pastry, ragout, lettuce, boiled egg, Javanese mustard, and pickled vegetables. Sangga buwana itself and every component to prepare it have the meaningful philosophy about God’s creations. It delivers important wishes and meanings to the newlywed couple in royal wedding ceremony. It was only served to the sultan, royal family of Yogyakarta, and their important guests. But nowadays, sangga buwana can be more easily found at restaurants, traditional markets or food festivals in Yogyakarta. The cultural preservation of sangga buwana has been conducted through cultural festivals, cooking workshops, and research development using local ingredients to prepare it which may support food diversification